Impact on Visceral Fat of male inactive and active older adults from Punjab, India - Pawandeep Kaur; Deol, Nishan Singh (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
This study aimed to investigate the impact on visceral fat of male inactive and active older adults.  Participants (N=180) inactive group (N=90) and active group (N=90) older adults from Punjab were selected to act as subjects for the study. The study was delimited to the older male inactive and active older adults recruited at age group 60 - 70, 71 - 80 and 81 - 90 years  respectively. For the purpose of data collection both the categories (Inactive and Active) of the subjects were divided into three categories i.e. category I (60-70 Years; N=30), category II (71-80 Years; N=30) and category III (81-90 Years; N=30) respectively. Body composition monitor OMRON (HBF-212) was used to measure the visceral fat. Statistical Package for Social Science (SPSS) version 23 was used to analyze the visceral fat of male inactive and active older adults, after collecting data One Way ANOVA (Analysis of Variance), Least Significant Difference (LSD) Post Hoc test was employed. The level of significance to test the hypotheses was 0.05, (P<0.05).  Results of the study found that there was a statistically significant difference in both the variables with a p-value of the visceral fat 0.03 (P <0.05) of male inactive and active older adults.   In conclusion, visceral fat changes with aging. The active age category 60-70 had demonstrated better on visceral fat than their inactive age category 60-70 insignificantly. The active age category 71-80 had demonstrated better visceral fat than the inactive age category 71-80 significantly. The active 81-90 had demonstrated insignificantly better visceral fat than their inactive age category 81-90.